Keluarga Politik Yasin Limpo Pada Pemilihan Kepala Daerah di Kabupaten Gowa Tahun 2015 - Rusnaedy, Zaldy; Purwaningsih, Titin (Jurnal Politik, 2018)
This article discusses the modality of Yasin Limpo’s family in the 2015 Gowa Regency local election. The modality itself consists of economic, social, cultural, and political capital. This research applies qualitative approach which shows that influential capitals are actually the legacy of resources owned by an influential older member of the family. As he acted as regents in previous terms he controlled resources which in turn signifi¬cantly generate public support to the candidates in the 2015 local election. This article argues that the inheritance of modality in the form of the legacies of flagship programs is the most influential capital. The superiority of the the Yasin Limpo family in the Gowa District is in fact getting stronger shown by the domination of members of the family that compete as the frontrunner candidates, Adnan Purichta Ichsan and Tenri Olle.